PENGGUNAAN BAHASA ALAY PADA BULLYING ANAK DI MEDIA SOSIAL - Rini Damayanti (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
Using the internet has become a routine most people. A wide variety of interesting social networking site became connoisseurs choice of media, one of which is the social network Facebook. The existence of facebook of course have positive and negative effects. As one of the negative impacts of the use of facebook is used as a medium where do bullying. The act of cyberbullying usually occurs in teenagers. The study aims to analyze how bullying occurs among students in social media using alay language, analyzed through qualitative research methods with descriptive and also with data collection using observation and documentation, the data obtained were analyzed using analysis model includes data reduction, data presentation, and conclusion. So from the process, it can be seen how the bullying occurred among students. The result of the analysis shows that bullying behaviours really happened among child and teenagers. Based on the analysis, the type of bullying messages consist of negative called-name, slammed opinion, threatened physical harm and underestimate opinion to the victims.